Spatial-temporal distribution characteristics, species selection, and influencing factors of cherry blossom scenic spots in China - Peng, Hongjun; Li, Ping; Zhang, Xinyi; Han, Yiwei; Sun, Rui; Zhang, Chunyan (Frontiers in Forests and Global Change, 2025)
Cherry blossom scenic spots attract numerous tourists during peak flowering seasons, significantly contributing to outdoor recreation, public health, and tourism development. Existing research has primarily focused on species classification, flowering period regulation, and localized landscape design. However, systematic studies examining these scenic spots’ temporal and spatial patterns remain scarce, hindering effective planning across varying latitudes and urban contexts. This study aims to fill this research gap by conducting spatiotemporal distribution analysis using ArcGIS, in conjunction with the geographical detector and sentiment perception measurement methods. Key findings from the analysis of 253 cherry blossom scenic spots in China include: (1) These spots are found in all provincial-level regions except Qinghai and Hainan, with Hubei Province having the highest concentration. The distribution has shifted from a discrete pattern to a clustering trend in high-density areas of North, East, and Central China, particularly Beijing, Shanghai, and Wuhan. (2) Main applications include parks, campuses, mountains, temples, and roadways, predominantly located in parks. (3) Variations in cherry blossom species and flowering periods are notable across regions, with diverse species in North, East, and Central China. (4) Economic status primarily influences distribution, alongside natural geographic and demographic factors, whose interactions enhance explanatory power. (5) The 10 most reviewed spots show positive visitor perceptions, with distinct emotional responses by region. (6) The layout and evolution of these spots result from both natural and socio-cultural influences. These findings support informed planning and development strategies for cherry blossom scenic spots in China.